Recurrencia de sindrome inflamatorio multisistemico asociado a infección por COVID-19: reporte de caso - Diego Andrés Rodríguez-Rangel (Asociación Colombiana de Infectología, 2023)
The COVID-19 pandemic has left millions of cases and deaths worldwide, in children the infection is less severe and has low mortality. A post-infectious entity called Systemic Multiinflammatory Syndrome (MIS-C) associated with COVID-19 infection is described, which has a mortality rate ten times higher than acute infection in children. MIS-C is characterized by sustained systemic inflammatory manifestations associated with fever and multiple system involvement. We present the case of a schoolgirl who presented a diagnosis of MIS-C with a good response to management and 11 months later, she presented a second episode that also responded to treatment. To date, we have not found in the literature the report of recurrence of MIS-C in children, such as the case presented by us, it marks an important precedent, inviting us to consider recurrence as a possibility in the case of a similar clinical presentation.